2009
DOI: 10.1038/sj.bjc.6605355
|View full text |Cite
|
Sign up to set email alerts
|

Humanised IgG1 antibody variants targeting membrane-bound carcinoembryonic antigen by antibody-dependent cellular cytotoxicity and phagocytosis

Abstract: BACKGROUND: The effect of glycoengineering a membrane specific anti-carcinoembryonic antigen (CEA) (this paper uses the original term CEA for the formally designated CEACAM5) antibody (PR1A3) on its ability to enhance killing of colorectal cancer (CRC) cell lines by human immune effector cells was assessed. In vivo efficacy of the antibody was also tested. METHODS: The antibody was modified using EBNA cells cotransfected with b-1,4-N-acetylglucosaminyltransferase III and the humanised hPR1A3 antibody genes. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…In keeping with our work on anti-CEA antibodies and with other studies, we have shown that immune mediated cetuximab killing of ERBB1 + CRC cell lines that express moderate to high levels of ERBB1 receptor occurs both by ADCC and ADCP (14,15).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In keeping with our work on anti-CEA antibodies and with other studies, we have shown that immune mediated cetuximab killing of ERBB1 + CRC cell lines that express moderate to high levels of ERBB1 receptor occurs both by ADCC and ADCP (14,15).…”
Section: Discussionsupporting
confidence: 90%
“…Previous evidence shows that the main mediators of ADCC in humans are natural killer (NK) cells (14,15). We have therefore checked that the cetuximab-mediated ADCC against the cell lines is effective at a NK cell: target cell ratio of 10:1 and is blocked by antibody to the FcγRIII receptor, as would be expected from our own and others previous results with cell line in vitro studies (Fig.…”
Section: Cetuximab-mediated Effects On Downstream Phosphorylation Insupporting
confidence: 53%
“…Previous studies have shown that changing the glycosylation pattern of the Fc portion of antibodies can influence their ability to elicit effector function by enhancing their binding affinity to FcγRIIIa on human immune cells. 14,27 We saw similar enhanced affinity to FcγRIIIa with SMIP-016 GV (Fig. 1C).…”
Section: Resultssupporting
confidence: 56%
“…NK cells are considered as one of the players because they rapidly elicit potent ADCC in vitro in comparison with freshly isolated monocytes or granulocytes (6,17,22,23) and infiltrate tumors in trastuzumab-treated patients (24). On the other hand, several preclinical studies in murine models convincingly demonstrated that macrophage subsets are primarily responsible for eliminating circulating and tissue B cells upon anti-CD20 mAb therapy and essentially excluded a role for NK cell-, T cell-or perforin-dependent mechanisms in vivo in those particular models (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%